Досвід країн Балтії та Грузії щодо протидії корупції в органах внутрішніх справ та можливість його використання в Україні - Чумак, В. В.; Chumak, V. V.; ORCID: http://orcid.org/0000-0002-6171-2250 (Право і безпека. – 2014. – № 4 (55). – С. 149-154, 2014)
Зазначено, що явище корупції має руйнівний характер і уповільнює економічний розвиток країни. Розглянуто та проаналізовано досвід країн Балтії та Грузії у сфері боротьби проти корупції в органах внутрішніх справ, а також доведено доцільність обрання саме цих держав. На підставі проведеного аналізу стратегічних антикорупційних програм країн Балтії та Грузії сформульовано деякі корисні закономірності, які можуть стати в нагоді під час створення антикорупційної стратегії України.

The article states that the phenomenon of corruption is destructive and slows down the economic development. The experience of the Baltic country and Georgia in the fight against corruption in law enforcement agencies, and the expediency of the election of these states are considered. Measures that were applied by Georgia, Latvia, Lithuania and Estonia to combat corruption in law enforcement agencies are considered. The article states that in the «anti-corruption» list among post-Soviet countries only Lithuania, Estonia and Latvia proceeded far ahead from former Soviet republics. Ukraine started its independence with some «starting» position. It is emphasized that Estonia could in the short term become a leader among the Baltic countries to combat corruption, ahead of its nearest neighbors – Lithuania and Latvia. On the basis of the analysis of strategic anti-corruption program in the Baltic States and Georgia there were formulated some useful patterns, that can be useful while creating anti-corruption strategy in Ukraine: 1. Systematic reforming. To overcome the corruption the applying of reforms is not enough. The key to success will cover all areas without exception. Single reform will be unsuccessful and eventually will be reduced to zero indestructible system. 2. Decent wages and benefits. A person treasures the civil service, if it offers the high wages, decent pensions and social benefits. 3. Providing logistical means: those that help the course of their professional duties, and those that will make the most control over the work of law enforcement. 4. Creation of an electronic system which will allow avoiding contact with government officials and law enforcement officials, and will help to keep track of the progress within the case. 5. Conducting the increase of level of education. A low level of corruption in developed countries.

Отмечено, что явление коррупции обладает разрушительным характером и замедляет экономическое развитие страны. Рассмотрен и проанализирован опыт стран Балтии и Грузии в сфере борьбы против коррупции, а также доказана целесообразность выбора именно этих государств. На основании проведенного анализа стратегических антикоррупционных программ против коррупции в странах Балтии и Грузии сформулированы некоторые полезные закономерности, которые могут пригодиться при создании антикоррупционной стратегии Украины.
Чумак В. В. Досвід країн Балтії та Грузії щодо протидії корупції в органах внутрішніх справ та можливість його використання в Україні / В. В. Чумак // Право і безпека. – 2014. – № 4 (55). – С. 149-154.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; Internal Affairs Agencies; органы внутренних дел; корупція в ОВС; зарубіжний досвід; зарубежный опыт; foreign experience; страны Балтии; країни Балтії; Грузія; антикорупційна стратегія; Грузия; коррупция в ОВД; антикоррупционная стратегия; corruption; law enforcement agencies; Baltic countries; Georgia; anti-corruption strategy; Естонія; Латвія; Литва; Эстония; Латвия; Estonia; Latvia; Lithuania